Osiris wavelets and Set wavelets - Guy Battle (Journal of Applied Mathematics)
An alternative to Osiris wavelet systems is introduced in two dimensions. The basic building blocks are continuous piecewise linear functions supported on equilateral triangles instead of on squares. We refer to wavelets generated in this way as Set wavelets. We introduce a Set wavelet system whose homogeneous mode density is 2/5. The system is not orthonormal, but we derive a positive lower bound on the overlap matrix.